Pengujian Sistem Pendukung Keputusan Metode Simple Additive Weighting dan Weighted Product dengan Matlab - Rikki, Alex (LPPM UNIKA Santo Thomas Medan, 2017)
The concept of a program to assist decision-making is currently developing very rapidly. Many methods are used to assist in the decision making process. One method that can be used to solve the Multi Attribute Decision Making (MADM) problem with the SAW, Weighted Product method and others. This is because the method is simple, easy to understand, computationally efficient and has the ability to measure the relative performance of decision alternatives in a simple mathematical form. The problem is that to solve a particular MADM case it may be difficult to determine which method is most relevant to solving certain cases. For the making of the system, it is necessary to pay attention to the interface that is easily understood by the user, but many researchers only emphasize how the method solves the problem, so that the results of the study are not optimal, because only limited to using software, such as excel and others. In this study the authors conducted a test of several methods in the SPK using Graphic User Interface based applications with MATLAB, this is because it makes it easier in terms of making input data in the form of a matrix. The application that is built consists of a Main Menu in which there is a sub menu file consisting of Form SAW and WP Form.